Immunotherapy Responsive Autoimmune Subacute Encephalitis: A Report of Two Cases - Manoj Mittal; Nancy Hammond; Sharon G. Lynch (Case Reports in Medicine)
Objective. To describe the clinical characteristics and radiological findings in two patients with subacute encephalitis associated with elevated serum voltage-gated potassium channel antibody (VGKCAb) and antithyroperoxidase (TPO) antibody. Case Reports. Case 1: 63-year-old woman was admitted for altered mental status and possible seizure activity. MRI brain showed hyperintensity in the bilateral hippocampal areas. She was positive for VGKCAb and anti-TPO antibodies. She was treated with steroids, IVIG, plasma exchange and azathioprine. After 8 months, she had marked improvement in her memory and seizures. Case 2: 61-year-old woman was admitted for video EEG monitoring of unclassified seizure and cognitive function decline. MRI of the brain showed mild hyperintensity in bilateral hippocampal areas and significant atrophy in the frontotemporal lesion. Anti-TPO antibody and VGKCAb were positive. She was treated with steroids, plasma exchange and azathioprine. After 9 months, she had marked improvement in her memory and seizures. Conclusion. Autoimmune subacute encephalitis appears to be an underdiagnosed entity. It is important to screen patients with subacute encephalitis for anti-TPO antibody and VGKCAb, particularly in the presence of seizures. Immunosuppressive therapy appears to be effective in treating this entity.